La década del cambio : diez aǫs de gobierno socialista : 1982-1992 / Alfonso Guerra, José Felix Tezanos (eds.) - Guerra, Alfonso (1940-) Tezanos, José Félix (Ciencias sociales)
1° ed. de 1992 y 2° ed. sin cambios de 1993